The Impacts of Chase Combining-based Retransmissions on LoRaWAN Performance - Stancanelli, Elvis M. G.; S. Filho, Francisco Helder C. dos (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2024.1392, 2024)
LoRaWAN technology stands out in wireless communication applications due to its low power consumption and long-range capabilities. However, using a retransmission mechanism to ensure reliable communication can increase overhead and computational complexity, negatively impacting throughput and energy efficiency. Achieving a balance between reliability and scalability poses a challenge in LoRaWAN. One probable solution to this challenge is implementing a soft combination of retransmitted versions, prioritizing reliability characteristics. However, this approach has not yet been explored in LoRaWAN. This study examines the potential impacts of utilizing a popular soft combination of retransmission in LoRaWAN, called chase combining, and assesses its reliability and efficiency. The numerical analysis indicates that the spread factor significantly affects the advantages of chase combining. The study’s outcomes suggest that appropriately using chase combining can significantly improve the success rates of packets. However, this may lead to a minor trade-off regarding increased latency and energy consumption.